Developing Smart Nanoparticles Responsive to the Tumor Micro-Environment for Enhanced Synergism of Thermo-Chemotherapy With PA/MR Bimodal Imaging - Luo, Mingfang; Lv, Yijie; Luo, Xunrong; Ren, Qingfa; Sun, Zhenbo; Li, Tianping; Wang, Ailing; Liu, Yan; Yang, Caixia; Li, Xianglin (Frontiers in Bioengineering and Biotechnology, 2022)
With the development of nanotechnology, a theranostics nanoplatform can have broad applications in multimodal image-guided combination treatment in cancer precision medicine. To overcome the limitations of a single diagnostic imaging mode and a single chemotherapeutic approach, we intend to combat tumor growth and provide therapeutic interventions by integrating multimodal imaging capabilities and effective combination therapies on an advanced platform. So, we have constructed IO@MnO2@DOX (IMD) hybrid nanoparticles composed of superparamagnetic iron oxide (IO), manganese dioxide (MnO2), and doxorubicin (DOX). The nano-platform could achieve efficient T2-T1 magnetic resonance (MR) imaging, switchable photoacoustic (PA) imaging, and tumor microenvironment (TME)-responsive DOX release and achieve enhanced synergism of magnetic hyperthermia and chemotherapy with PA/MR bimodal imaging. The results show that IMD has excellent heating properties when exposed to an alternating magnetic field (AMF). Therefore, it can be used as an inducer for tumor synergism therapy with chemotherapy and hyperthermia. In the TME, the IMD nanoparticle was degraded, accompanied by DOX release. Moreover, in vivo experimental results show that the smart nanoparticles had excellent T2-T1 MR and PA imaging capabilities and an excellent synergistic effect of magnetic hyperthermia and chemotherapy. IMD nanoparticles could significantly inhibit tumor growth in tumor-bearing mice with negligible side effects. In conclusion, smart IMD nanoparticles have the potential for tumor diagnosis and growth inhibition as integrated diagnostic nanoprobes.